Evaluation of Bone Metastases by 18F-Choline PET/CT in a Patient with Castration-Resistant Prostate Cancer Treated with Radium-223. Issue 1 (January 2017) - Scalzi, Piera; Baiocco, Cinzia; Genovese, Sabrina; Trevisan, Antonella; Sirotova, Zuzana; Poti, Carlo
Background: To date, bone metastases remain the main cause of morbidity and mortality in patients with metastatic castration-resistant prostate cancer (mCRPC). Therefore, the combination of accurate early detection of bony disease and effective treatment of these lesions is crucial in the management of mCRPC patients, but clinical trials specifically designed to test novel approaches are currently lacking. Case Description: This report describes the case of a 74-year-old male with bone mCRPC and symptomatic and biochemical progression, who underwent radium-223 therapy, following previous treatment failure. 18F-choline positron emission tomography (PET)/computed tomography (CT) was used to assess changes in skeletal tumor activity before and after radium-223. Changes in prostate-specific antigen and alkaline phosphatase were also determined. 18F-choline PET/CT showed that treatment with radium-223 was able to effectively reduce bone metastatic disease, and this was accompanied by an excellent metabolic response. Conclusions: In clinical practice, metabolic assessment of lesions by 18F-choline PET/CT following radium-223 seems a valid approach to monitor treatment response. Until results from clinical trials become available, reporting of single cases relating to data on the use of this technique remains paramount.